Angiography‐derived versus invasively‐determined index of microcirculatory resistance in the assessment of coronary microcirculation: A systematic review and meta‐analysis. Issue 7 (2nd April 2022) - Fernández‐Peregrina, Estefania; Garcia‐Garcia, Hector M.; Sans‐Rosello, Jordi; Sanz‐Sanchez, Jorge; Kotronias, Rafail; Scarsini, Roberto; Echavarria‐Pinto, Mauro; Tebaldi, Matteo; De Maria, Giovanni L.
Abstract: Background: The index of microvascular resistance (IMR) is an established tool to assess the status of coronary microcirculation. However, the need for a pressure wire and hyperemic agents have limited its routine use and have led to the development of angiography‐derived pressure‐wire‐free methods (angiography‐derived IMR [IMRAngio]). In this review and meta‐analysis, we aim to assess the global diagnosis accuracy of IMRAngio versus IMR. Methods: A systematic review of the literature was performed. Studies directly evaluating IMRAngio versus IMR were considered eligible. Pooled values of diagnostic test and summary receiver operator curve were calculated. Results: Seven studies directly comparing IMRAngio versus IMR were included (687 patients; 807 vessels). Pooled sensitivity, specificity, +likelihood ratio (LR), and −LR were 82%, 83%, 4.5, and 0.26 respectively. Pooled accuracy was 83% while pooled positive predictive value and negative predictive value were 76% and 85%, respectively. Comparable results were obtained when analyzing by clinical scenario (acute and nonacute coronary syndromes). Conclusion: IMRAngio shows a good diagnostic performance for the prediction of abnormal IMR.